Superhydrophobic polypropylene surfaces prepared with TiO 2 nanoparticles functionalized by dendritic polymers - Contreras, Cintia Belén (2018)
Hybrid inorganic–organic nanomaterials have received increasing interest due to the possibility of implementing different functions and characteristics within a single material. Their functionalities are a consequence of the synergy of the properties of distinct building blocks and are related to their varied natures and spatial locations. In this work, we present the development of superhydrophobic properties on polypropylene (PP) surfaces using hybrid nanomateriales from TiO 2 nanoparticles (NPs) and dendronized polymers. The dendron acryl Behera's amine was successfully grafted on the TiO 2 NP surfaces by Surface-Initiated Atom Transfer Radical Polymerization (SI-ATRP) and a core-brush material was obtained. Finally, PP substrates were coated with NP hybrids to produce superhydrophobic surfaces with water contact angles of over 158 degrees. Controlling the organic silane concentration on the TiO 2 NPs allowed the dendronized process to be driven and thereby permitted the selection of specific wettability properties on PP substrate surfaces with high water adhesion or self-cleaning conditions. This dendronized effect with consequent steric congestion of the polymeric brushes on the NPs changed their behaviors from Wenzel to the Cassie Baxter state. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 2019–2029.